Równania Macierzowe Tarczownicy Pryzmatycznej - Poplewska, J.; Wrześniowski, K. (Engineering Transactions, 1972)
In the paper a direct method of calculation of prismatic, simply supported folded plate structures is described. The method discussed was originally proposed by Scordelis [4], and due to matrix formu1ation it can be used to the structural analysis with the use of digital computers. A numerical example is given in the paper.